Orita ibadan journal of religious studies (2017)
Trafficking has been described as all activities that entail the conveyance, sheltering and trade in humans within or across national and international boundaries through deceit, kidnap, or other forceful means with the intent of engaging victims in forced services or labour. Trafficking, particularly in women and children, is considered by the international community a fast growing global avarice. Dominant features of the globalised trade include: domestic servitude and prostitution which is different in comparison to the context of the Trans-Atlantic Slave Trade. This study takes on prostitution in trafficking, engaging the inherent potential and the existing influence of the literary writer to conscientise, redefine and reposition the society. This is done by examining portrayals of character-types, development of the plot and depths of the thematic preoccupation and literary elements which have contributed immensely to the redefinition of Africa in Africa, and Africa before the international community. This paper employs Akachi Adimora-Ezeigbo’s Trafficked and Chika Unigwe’s On Black Sisters’ Street, novels that thematically dwell on this global concern. It critically engages national and international postures in examining dimensions of trafficking such as: trafficking as an industry and cartel, prostitution as a vocation for the trafficked, portrayals of the stake holders, portrayals of the victims, value systems that promote the desire of young women to live and earn money abroad, and the psychological, physiological as well as sociological import of being trafficked and being a sex- slave. Trafficked and On Black Sisters ’Street are Nigerian literary templates that serve as conscientisation and deterrence for the class of women this new tool of trade targets.